What types of U.S. companies join the United Nations Global Compact? An empirical analysis of voluntary initiative engagement comparing the competitive advantage, regulatory avoidance, and new moral marketplace approaches - Watne, Zachary Patrick, author; Stretesky, Paul, advisor; Shelley, Tara O'Connor, committee member; Stevis, Dimitris, committee member (Colorado State University. Libraries, 2010)
Previous literature on voluntary initiatives indicates that companies are more likely to join if they are large, diverse, profitable and are experiencing more regulatory oversight. While these findings are interesting, they have yet to be replicated among a sample of United States companies in the case of the United Nations Global Compact. Thus, this study draws upon corporate social responsibility literature as it relates to the United Nation's Global Compact to explore the relationship between Global Compact participation, company characteristics, regulatory oversight, and regulatory violations. The data for this analysis comes from the United Nations Global Compact Office, the United States Securities and Exchange Commission EDGAR database, the Environmental Protection Agency's Enforcement & Compliance History Online Database, the Dun & Bradstreet Million Dollar Database, Reference USA, along with selected corporate websites. The sample consists of 70 companies that joined the Global Compact and 70 companies that did not join the Global Compact. Logistic regression analysis suggests that the number of Securities and Exchange Commission litigation documents filed against each company increases the likelihood of Global Compact participation, as does the size of the company (seen with both sales totals and employees per company); additionally, companies based in manufacturing are also more likely to sign into the Global Compact. Surprisingly, previous environmental compliance was not associated with participation in the Global Compact. This finding suggests that U.S. companies that join the Global Compact are not "good" or "bad" environmental actors. This study is unique in that findings suggest companies that join the Global Compact appear to be driven primarily by economic regulation as opposed to environmental regulation.
Keywords: Global Compact; voluntary initiatives; compliance; regulation; global compact; corporate social responsibility; Social responsibility of business -- United States; International business enterprises -- Moral and ethical aspects; Corporate culture -- United States; United Nations